The Effect of Virtual Science Teaching Model on Scientific Creativity and Learning Outcomes - Wicaksono, Iwan; Erlina, Nia (Jurnal Pendidikan MIPA, 2024)
VS-TM (Virtual Science Teaching Model) is a learning model that applies a virtual-assisted scientific approach and is implemented to improve scientific creativity and student understanding in science subjects. This study aims to determine the effect of VS-TM on scientific creativity and student learning outcomes. This research was conducted at SMPN 1 Bangorejo, which was carried out in the even semester of the 2023/2024 school year, precisely in February 2024. The study population was all students of SMPN 1 Bangorejo Class VIII. Sample determination. Determination of the sample using the homogeneity test that had previously been carried out before conducting the research. This type of research is a two-class quasi-experimental, including experimental and control classes. There are two data analysis techniques used, namely normality testing and hypothesis testing. Normality test using Kolmogorov Smirnov, hypothesis test using Mann-Whitney U test. The results of this study are that the that the VS-TM model affects the scientific creativity and learning outcomes of junior high school students.         Keywords: VS-TM (virtual science teaching model), scientific creativity, and learning outcomes.DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp440-452